Pengaruh Kegunaan, Kemudahan, dan Kepercayaan Terhadap Perilaku Pengguna Aplikasi Electronic Marketplace Agree Mart - Natalia, Sora Maria; Sadeli, Agriani Hermita; Natawidjaja, Ronnie Susman; Trimo, Lucyana (Universitas Galuh, 2024)
Advancements in technology and information drive changes in economic activity, one of which is marked by the emergence of electronic marketplace applications. Electronic marketplace applications specifically for food products are not growing rapidly compared to other electronic marketplace applications, including Agree Mart. This study extends the Technology Acceptance Model (TAM) theory and user trust to determine the behavior of Agree Mart application users. This study aims to describe the behavior of users of the Agree Mart electronic marketplace application. This study uses a quantitative method assisted by the application of SMART PLS 4 with descriptive analysis techniques and simple random sampling techniques. The respondents of this study were 72 respondents who were users of the Agree Mart application. The results showed that the level of acceptance of electronic marketplace technology for food products was in a good category.